Toward a view of integrating corporate sustainability into strategy: A systematic literature review - Hong Linh Nguyen; Dominik K. Kanbach (Corporate Social Responsibility and Environmental Management, 2023)
In recent years, research on corporate sustainability integration strategies has witnessed a significant growth in interest. However, contributions remain disjointed and fragmented, preventing the emergence of a cohesive understanding of the current research state. This study uses a systematic review of 126 articles from Web of Science (WoS) and Ebsco to extract a seven-dimensional integrated view of corporate sustainability integration strategies. Our review's contributions are threefold: (1) we enrich the corporate sustainability strategies literature by identifying the focuses and themes of recent publications; (2) we address the research's fragmentation issue by presenting the sustainability implementation strategies in an integrated view with the essential interdependencies shown at different hierarchical levels and across organizational dimensions simultaneously, (3) we present the theoretical and managerial implications and discuss in detail the crucial interdependencies of sustainability integration strategies. The study finishes with a conclusion highlighting potential avenues for future research.
Keywords: 650; corporate environmental strategy; corporate sustainability; corporate sustainability integration; strategy